The first instrument for complex PTSD assessment: psychometric properties of the ICD-11 Trauma Questionnaire - Rocha,José (2020)
Objective: The ICD-11 Trauma Questionnaire (ITQ) was developed as a joint effort by researchers from several countries to evaluate post-traumatic stress (PTSD) and complex-PTSD (C-PTSD) symptoms. This study is part of a multi-center international collaborative research project that aims to provide psychometric support for this initial instrument in different languages, considering the specific contexts related to complex traumatization. This study verified the psychometric characteristics of the Portuguese version of the ITQ, evaluating symptoms beyond those described the existing literature. Methods: We examined the results of a convenience sample totaling 268 Portuguese and Angolan participants. Two instruments were applied: the ITQ, which evaluates symptoms resulting from a traumatic life event, and the Life Events Checklist (LEC), which evaluates stressful life events. The general characteristics of the scales are described, and reliability analysis and validity studies were performed. Results: Cronbach’s alpha varied between 0.84 and 0.88, and the exploratory factorial analysis results were consistent with the concept of C-PTSD, with five components explaining 61.58% of scale variance. Conclusion: The results suggest good psychometric characteristics for the Portuguese version of the ITQ, and thus it can be included in protocols intended evaluating complex traumatic symptoms.